A Neanderthal/Denisovan GLI3 variant contributes to anatomical variations in mice - Agata, Ako; Ohtsuka, Satoshi; Noji, Ryota; Gotoh, Hitoshi; Ono, Katsuhiko; Nomura, Tadashi (Frontiers in Cell and Developmental Biology, 2023)
Changes in genomic structures underlie phenotypic diversification in organisms. Amino acidchanging mutations affect pleiotropic functions of proteins, although little is known about how mutated proteins are adapted in existing developmental programs. Here we investigate the biological effects of a variant of the GLI3 transcription factor (GLI3 R1537C ) carried in Neanderthals and Denisovans, which are extinct hominins close to modern humans. R1537C does not compromise protein stability or GLI3 activator-dependent transcriptional activities. In contrast, R1537C affects the regulation of downstream target genes associated with developmental processes. Furthermore, genome-edited mice carrying the Neanderthal/Denisovan GLI3 mutation exhibited various alterations in skeletal morphology. Our data suggest that an extinct hominin-type GLI3 contributes to speciesspecific anatomical variations, which were tolerated by relaxed constraint in developmental programs during human evolution.